Elimination of Falciparum Malaria and Emergence of Severe Dengue: An Independent or Interdependent Phenomenon? - Bygbjerg, Ib C.; Simonsen, Lone; Schiøler, Karin L. (Frontiers in Microbiology, 2018)
The global malaria burden, including falciparum malaria, has been reduced by 50% since 2000, though less so in Sub-Saharan Africa. Regional malaria elimination campaigns beginning in 1940s, up-scaled in 1950s, succeeded in 1970s in eliminating malaria from Europe, North America, the Caribbean (except Haiti) and parts of Asia and South- and Central America. Dengue has grown dramatically throughout pantropical regions since the 1950s, first in Southeast Asia in large-scale epidemics including severe dengue, though mostly sparing Sub-Saharan Africa. Globally, the WHO estimates 50 mio dengue infections every year, while others set estimate almost 400 mio cases, with 100 mio clinical cases. Curiously, despite wide geographic overlap between malaria and dengue-endemic areas, published reports of co-infections have been scarce until recently. Superimposed acute dengue infection might be expected to result in more severe combined disease because both pathogens can induce shock and haemorrhage. However, a recent review found no reports on more severe morbidity or higher mortality associated with co-infections. Cases of severe dual infections have almost exclusively been reported from South America, and predominantly in persons infected by Plasmodium vivax. The first person with concurrent malaria and dengue was reported in 2005 in a traveler to West Africa, and serological evidence of dengue is also high in sub-Saharan Africa. We hypothesize that malaria infection may partially protect against dengue - in particular falciparum malaria against severe dengue - and that this inter-species cross-protection may explain the near absence of severe dengue from the Sub-Saharan region and parts of South Asia until recently. We speculate that malaria infection elicits cross-reactive antibodies or other immune responses that infer cross-protection, or at least partial cross-protection, against symptomatic and severe dengue. Plasmodia have been shown to give rise to polyclonal B-cell activation and to heterophilic antibodies, while some anti-dengue IgM tests have high degree of cross-reactivity with sera from malaria patients. In the following, the historical evolution of falciparum malaria and dengue is briefly reviewed, and we explore early evidence of subclinical dengue in high-transmission malaria areas as well as conflicting reports on severity of co-morbidity. We also discuss examples of other interspecies interactions.